1981
DOI: 10.1111/j.1460-2466.1981.tb00449.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Family Communication in Consumer Learning

Abstract: One of the most important factors in the child's acquisition of consumer skills, knowledge, and attitudes is believed to be intrafamily communication about consumption (4, 10, 23). But rather than simply being linked to the quantity of interaction, effective consumer learning has also been found to be closely tied to the patterns or quality of communication that takes place within the home (12, 13). This is in line with family communication patterns (FCP) research in political socialization, where patterns hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
121
4
12

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 9 publications
11
121
4
12
Order By: Relevance
“…Materialism has long been of interest to consumer researchers, but research has centered on adult consumers, not on children or teens. A small flurry of research appeared in the 1970s that found materialism in adolescents to be correlated with factors such as ineffective family communication patterns, greater peer communication, and higher levels of television viewing (Churchill and Moschis 1979;Moore and Moschis 1981;Moschis and Churchill 1978;Moschis and Moore 1979). Since then, only a handful of consumer behavior articles on the topic have appeared, finding higher levels of materialism in young consumers with materialistic parents (Goldberg et al 2003), disrupted families (Rindfleisch, Burroughs, and Denton 1997;Roberts, Tanner, and Manolis 2005), less affluent households (Goldberg et al 2003), and greater susceptibility to influence from peers and marketing promotions (Achenreiner 1997;Goldberg et al 2003).…”
Section: John Deighton Served As Editor and Laura Peracchio Served Asmentioning
confidence: 99%
“…Materialism has long been of interest to consumer researchers, but research has centered on adult consumers, not on children or teens. A small flurry of research appeared in the 1970s that found materialism in adolescents to be correlated with factors such as ineffective family communication patterns, greater peer communication, and higher levels of television viewing (Churchill and Moschis 1979;Moore and Moschis 1981;Moschis and Churchill 1978;Moschis and Moore 1979). Since then, only a handful of consumer behavior articles on the topic have appeared, finding higher levels of materialism in young consumers with materialistic parents (Goldberg et al 2003), disrupted families (Rindfleisch, Burroughs, and Denton 1997;Roberts, Tanner, and Manolis 2005), less affluent households (Goldberg et al 2003), and greater susceptibility to influence from peers and marketing promotions (Achenreiner 1997;Goldberg et al 2003).…”
Section: John Deighton Served As Editor and Laura Peracchio Served Asmentioning
confidence: 99%
“…Nesta área, encontramse resultados conflitantes na literatura. Alguns estudos com adolescentes assinalam uma diminuição dos níveis de materialismo relacionada ao aumento da idade; outros concluem que o materialismo é um traço que se mantém estável ao longo do desenvolvimento, não sendo possível apontar diferenças significativas entre a adolescência inicial e final (Chaplin & Jon, 2007;Goldberg et al, 2003;Moore & Moschis, 1981;Schaefer et al, 2004).…”
Section: Discussionunclassified
“…Since family is the first place where social environment for modelling is formed, parents have an important role in bringing the next generation consumption attitudes. Previous literature emphasizes the effect of the mother"s consumption attitudes and behaviors on the child"s (Moore and Moschis, 1981). The main objective of this research is to investigate the effect of parents on the individual"s environmentally responsible consumption awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, family has an important role in upbringing the next generation as responsible and environmentally conscious consumers (Moore and Moschis, 1981). Especially mothers have a powerful impact on raising environmentalists and conscious children (Moore and Stephens, 1975).…”
Section: Introductionmentioning
confidence: 99%